Analisis Fakto-Faktor Yang Mempengaruhi Good Corporate Governance Pada Perusahaan Sub Sektor Perbankan Yang Terdaftar di Bursa Efek Indonesia - Ebi Murdani; Debi Carolina (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2019)
Good Corporate Governance can be interpreted as a system, process, and a set of rules governing the relationship between various parties that are in the sense of a stakeholder, in the case of a narrow relationship between shareholders, the board of Directors, and the Board of Commissioners achieving the company's objectives. There are five principles in Good Corporate Governance (GCG), namely transparency, accountability, responsiveness, independence, and equality. This research aims to test the influence of the company's characteristics on Good Corporate Governance (GCG). The formulation of the problem in this research is how the influence of profitability, leverage, managerial ownership, and institutional ownership of Good Corporate Governance is. This research analyzes the characteristics of the company as a factor affecting Good Corporate Governance (GCG). The characteristics of the company are divided into several variables namely profitability, leverage, managerial ownership, and institutional ownership. The population in this research is a banking sub-sector company listed on the Indonesian stock exchange in 2015-2017. The sampling method in this study is purposive sampling. Based on sample determination, 5 companies are acquired. The analytical techniques used in this research are data analysis methods. The results showed that profitability, leverage, managerial ownership, institutional ownership has an effect on Good Corporate Governance.